Prevalence of Trichomonas vaginalis Among Female Patients Attending Some Medical Facilities in Parts of Southern Taraba State, North East Nigeria - Cockeye, Brown Samuel Tamuno; Ify, Agwaranze Dawn; Wama, Yusuf Precious; Pelentovun, James Samuel (Darul Yasin Al Sys, 2026)
Trichomoniasis, caused by Trichomonas vaginalis, remains one of the most prevalent non-viral sexually transmitted infections and poses a substantial public health burden, particularly in low-resource settings. This study aimed to determine the prevalence of T. vaginalis infection and identify its associated risk factors among female patients attending health facilities in Wukari, Ibi, and Donga Local Government Areas of Southern Taraba State, Nigeria. A hospital-based cross-sectional design was employed involving 522 female patients aged 18–59 years. High vaginal swab samples were collected and examined microscopically using wet mount preparation, while demographic, behavioural, and awareness-related data were obtained through structured questionnaires. The overall prevalence of T. vaginalis infection was 4.4%, with substantial variation across locations, being highest in Donga (9.2%), followed by Ibi (2.9%) and Wukari (1.1%). Infection was more frequently observed among women aged 30–41 years, widowed individuals, and those without formal education; however, these demographic variables were not statistically significant (P > 0.05). In contrast, behavioural factors, particularly multiple sexual partnerships and inconsistent condom use, showed significant associations with infection. Awareness of sexually transmitted infections and T. vaginalis was generally low and was not significantly associated with infection risk (P > 0.05). The study concludes that behavioural factors are the principal drivers of T. vaginalis transmission in this population. These findings underscore the need for targeted interventions that integrate health education, safer sexual behaviour promotion, and improved access to screening services to reduce the burden of trichomoniasis in the region.